Similarity in Faces and How it is Influenced by Proximity - Janek, Ján (SIAK-Journal, 2020)
The aim of this work was to attempt to replicate the finding by Casasanto (Casasanto 2008) who studied the relationship between similarity and proximity in abstract words, unfamiliar faces and common objects and one of his findings (upon which this research paper is built) was that the closer faces are to each other, the more dissimilar they appear. And to test a possible explanation. Casasanto’s paper used the conceptual metaphor theory that similarity is closeness, however his results suggested that while words are judged to be more similar when presented spatially close, faces are judged to be more different. This project explored this phenomenon further and studied it in two separate experiments by testing both similarity of pairs of faces and accuracy in deciding whether they are of the same person over two experiments. Next, this experiment was to try and provide a potential explanation for this effect, which is the secondary hypothesis: faces distort their immediate surrounding which was studied by testing the point of subjective equality of two vertical and straight lines - one near and one further from an unfamiliar face. Should the line closer to the face be distorted, it would help provide an explanation as to why faces that are closer together might be judged as different. Regarding the primary hypothesis, no effect of distance was found for either the similarity rating or the matching task. Bayesian analysis provided support of the null hypothesis. However, there was evidence for the secondary hypothesis. There appears to be no effect present on similarity and accuracy when manipulating the distance between two unfamiliar faces. There is an effect however when the face distorted the line that was closer to it. A second experiment replicated the original study by Casasanto more exactly, presenting the two faces sequentially, rather than simultaneously. Again, however, no effect of distance was found; results were consistent with the first experiment.